DISFLUENCY PATTERNS AND PHONOLOGICAL SKILLS NEAR STUTTERING ONSET - Gregg, Brent Andrew (2012)
There is a substantial amount of literature reporting the incidence of phonological difficulties to be higher for children who stutter when compared to normally fluent children, suggesting a link between stuttering and phonology. In view of this, the purpose of the investigation was to determine whether, among children who stutter, there are relationships between phonological skills and the initial characteristics of stuttering. That is, close to the onset of stuttering, are there differences in specific stuttering patterns between children who exhibit minimal and moderate phonological deviations in terms of frequency of stuttering and length of stuttering events? Twenty-nine preschool children near the onset of stuttering, ranging in age from 29 to 49 months, with a mean of 39.17 months, were divided into two groups based on the level of phonological ability: minimal phonological deviations and moderate phonological deviations. The children’s level of stuttering-like disfluencies was examined. Results revealed no statistically significant differences in the stuttering characteristics of the two groups near onset, calling into the question the nature of the stuttering-phonology link.